Analisis Kebermanfaatan Aplikasi Panduan Diet untuk Anak Penderita Demam Berdarah - Purwaningrum, Sri Wulan; Saurina, Nia; Adisusilo, Anang Kukuh (Universitas Ahmad Dahlan, 2017)
Background: Dengue fever is a susceptible disease which attack almost Indonesian citizen, based on Indonesia Ministry at 25th January 2015 Indonesia have 38 cities and each of them already reached 1.054 peoples, and 25 of them has been passed away. Method: This research is a descriptive qualitative. The aim of this study to give rate for application that has been made. The research was conducted by interviewed the parents who have childrenÂ with dengue fever. The research instrument was checklist using Likert scale. This research conducted in threeÂ primary health care (puskesmas) which is Puskesmas Wonokromo, Puskesmas Jagir, and Puskesmas Sukolilo. The aim of the study was to understand the perceived usefulness, ease of use, ease of learning, satisfaction screen, terminology and system information, system capabilities, and overall reaction to the software. Results: This application already tested to three different groups and they are: two people as nutritionist, five people as nurses and 20 parents who have children suffer dengue fever. The result of test was numbered as 81% from nutritionist, 89% from nurses and 81% of parents declared that the application is a very good. Conclusion: Target group of application trials stated that the application can be categorized as an excellent tool and can be used by parents to get information about food and drink needs for children with dengue fever.